Inverse synthetic aperture radar-based covert system for human identification - GEREN, WILLIAM P; MORGAN, DOUGLAS P (2006)
A method, apparatus, and computer readable medium are provided for creating a quantitative, three-dimensional representation of a surface of a human subject. Data representing a physical appearance of a human subject is gathered using inverse synthetic aperture radar. A source signal is directed toward the human subject as the target rotates through a range of motion and a return signal is collected. The returned signal is transformed into a quantitative representation of the surface data. The quantitative representation can be added to an archive or can be checked against an archive to determine if the human target is indexed in the archive.